1989
DOI: 10.1080/00913847.1989.11709735
|View full text |Cite
|
Sign up to set email alerts
|

Body Checking in Pee Wee Hockey

Abstract: In brief: Two separate studies were done to determine the effects of body checking at the Pee Wee level. Study 1 evaluated eight of the smallest and eight of the largest players from leagues that allowed body checking. The players were measured for height, weight, grip strength, maximal skating speed, impact force during a body check, and speed of skating at impact. Significant morphologic differences (p <.05) between small and large players were reflected in forces of impact. Study 2 investigated the incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Eleven of the 22 studies did not provide an effect estimate12 16 18 21 23 25 29–32 and of these, six also did not report any assessment of random error (ie, confidence limits or p-values) 12 21 23 30–32. Effect estimates from six studies were calculated where data were available 12 16 21 23 29 31. Other general limitations are summarised.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven of the 22 studies did not provide an effect estimate12 16 18 21 23 25 29–32 and of these, six also did not report any assessment of random error (ie, confidence limits or p-values) 12 21 23 30–32. Effect estimates from six studies were calculated where data were available 12 16 21 23 29 31. Other general limitations are summarised.…”
Section: Resultsmentioning
confidence: 99%
“…1,5,11,13,16 Body checking has also been established as an important contributing factor for fractures and other types of injury. 1,5,14,15 All but 1 study that met our inclusion criteria found an increased risk of injuries due to body checking. 12 The results of this study have been questioned on the definition of the study denominator and possible underreporting of injuries in the body checking group.…”
Section: Discussionmentioning
confidence: 98%
“…Data from several studies [11][12][13][14][15] were extracted and synthesized into usable data for this review. All other data were extracted as recorded in the original studies.…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…The largest boys were also more than twice as strong (grip strength) and generated about 1.7 times more force at impact and about 1.2 times greater speed at impact under experimental conditions than the smallest boys. 39 The size and maturity differences among young athletes in contact sports and their relationship to risk of injury should be a concern but have not been adequately studied.…”
Section: Discussionmentioning
confidence: 99%